Noise-Robust Heart Rate Estimation Algorithm from Photoplethysmography Signal with Low Computational Complexity - Shin, JaeWook; Cho, Jaegeol (Journal of healthcare engineering, 2019)
This paper introduces a noise-robust HR estimation algorithm using wrist-type PPG signals that consist of preprocessing block, motion artifact reduction block, and frequency tracking block. The proposed algorithm has not only robustness for motion noise but also low computational complexity. The proposed algorithm was tested on a data set of 12 subjects and recorded during treadmill exercise in order to verify and compare with other existing algorithms.